b^2 - 2ab - a^2 = 0 Can I use the quadratic formula to solve for b? If so, how? I have tried repeated times and I keep getting the wrong answer...
Follow Math Help Forum on Facebook and Google+
Originally Posted by bearej50 b^2 - 2ab - a^2 = 0 Can I use the quadratic formula to solve for b? If so, how? I have tried repeated times and I keep getting the wrong answer... You can assuming a is constant $\displaystyle b = \frac{2a \pm \sqrt{4a^2-(4 \cdot 1 \cdot -(a^2))}}{2}$ $\displaystyle b = \frac{2a \pm 2a \sqrt{2}}{2} = a(1 \pm \sqrt{2})$
View Tag Cloud